Prospects of BOT (Build-Operate-Transfer) Projects for Infrastructure Development in Nepal - Shrestha, Santosh Kumar (Journal of the Institute of Engineering, 2011)
Infrastructure development is one of the top priorities in a country's economic progress. Planned and well connected infrastructure services attract foreign direct investments and boost local investments. To meet the present and future demand for infrastructure development, developing and least developed countries like Nepal always face scarcity of their own resources. To mitigate the shortage of the Government's funds for infrastructure developments, the Build-Operate-Transfer (BOT) mode of financing has been a model in many countries. Considering the BOT project successes in Malaysia, Thailand, the Philippines and other countries, and following Khimti-I and the United World Trade Center building, Nepal must seriously consider having more BOT projects. Especially in its urgently needed infrastructure such as Hydropower generation, roads, bridges, telecommunications, water supply, waste disposal, etc. Key Words: Build Operate Transfer; BOT; Public Private Partnership DOI: http://dx.doi.org/10.3126/jie.v8i1-2.5104 Journal of the Institute of Engineering Vol. 8, No. 1&2, 2010/2011 Page: 138-142 Uploaded Date: 20 July, 2011